Inconel 718 two ways: Powder bed fusion vs. directed energy deposition - Chechik, Lova; Todd, Iain (Additive Manufacturing Letters, 2023)
Additive manufacturing (AM) research has grown massively in the last few decades, with applications ranging from the medical sector to automotive. AM of nickel superalloys is of great interest for the aerospace sector due to their mechanical performance at increased temperatures. Components were manufactured using the two most common metallic AM processes, laser powder bed fusion (L-PBF) and laser directed energy deposition (L-DED). Microstructural and mechanical properties were compared and contrasted between the two processes, showing that despite the processes fundamentally being based on the same physical phenomena, the difference in scale between the processes stops them from being directly comparable. As such, alloy design and processing window development must be performed with a specific application and process in mind.<br
Keywords: Additive manufacturing; Laser deposition; Powder bed fusion; Directed energy deposition; Nickel superalloys